2005
DOI: 10.5483/bmbrep.2005.38.2.211
|View full text |Cite
|
Sign up to set email alerts
|

4-Acetoxyscirpendiol of Paecilomyces tenuipes Inhibits Na+/D-Glucose Cotransporter Expressed in Xenopus laevis Oocytes

Abstract: Cordyceps, an entomopathogenic fungus, contains many health-promoting ingredients. Recent reports indicate that the consumption of cordyceps helps reduce blood-sugar content in diabetics. However, the mechanism underlying this reduction in circulatory sugar content is not fully understood. Methanolic extracts were prepared from the fruiting bodies of Paecilomyces tenuipes, and 4-beta acetoxyscirpendiol (4-ASD) was eventually isolated and purified. Na + /Glucose transporter-1 (SGLT-1) was expressed in Xenopus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Besides cordycepin and polysaccharides (Yin et al 2007), a number of bioactive constituents have been reported from P. tenuipes. These include: tenuipesine A (Kikuchi et al 2004a), spirotenuipesine A and B (Kikuchi et al 2004b), paecilomycine A, B, and C (Kikuchi et al 2004c), 4b-acetoxyscirpene-3, 15-diol (Nam et al 2001;Oh et al 2001;Yoo et al 2005), ergosterol (Nam et al 2001), and beauvericin and its analogues (Nilanonta et al 2000(Nilanonta et al , 2002. Moreover, phthalic acid, stearic acid, di (2-ethylhexyl) phthalate, and cholesterol were also reported from this mushroom (Song et al 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Besides cordycepin and polysaccharides (Yin et al 2007), a number of bioactive constituents have been reported from P. tenuipes. These include: tenuipesine A (Kikuchi et al 2004a), spirotenuipesine A and B (Kikuchi et al 2004b), paecilomycine A, B, and C (Kikuchi et al 2004c), 4b-acetoxyscirpene-3, 15-diol (Nam et al 2001;Oh et al 2001;Yoo et al 2005), ergosterol (Nam et al 2001), and beauvericin and its analogues (Nilanonta et al 2000(Nilanonta et al , 2002. Moreover, phthalic acid, stearic acid, di (2-ethylhexyl) phthalate, and cholesterol were also reported from this mushroom (Song et al 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Besides cordycepin and polysaccharides (Yin et al 2007), a number of bioactive constituents have been reported from P. tenuipes. These include: tenuipesine A (Kikuchi et al 2004a), spirotenuipesine A and B (Kikuchi et al 2004b), paecilomycine A, B, and C (Kikuchi et al 2004c), 4b-acetoxyscirpene-3, 15-diol (Nam et al 2001;Oh et al 2001;Yoo et al 2005), ergosterol (Nam et al 2001), and beauvericin and its analogues (Nilanonta et al 2000(Nilanonta et al , 2002. Moreover, phthalic acid, stearic acid, di (2-ethylhexyl) phthalate, and cholesterol were also reported from this mushroom (Song et al 2007).…”
Section: Discussionmentioning
confidence: 86%